Public Policy and Venture Capital Backed Innovation - Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper discusses the role of public policy towards the venture capital industry. The model emphasizes four margins: supply of entrepreneurs due to career choice, entry of venture capital funds and search for investment opportunities, entrepreneurial effort and venture capital advice during the start-up period, and introduction of new goods by successful start-ups. The paper considers short- and long-run comparative static and welfare effects of policy reform with regard to capital gains taxation, innovation subsidies, public R&D spending and other policy initiatives.
Keywords: 330; innovation; venture capital; double moral hazard; public policy